2012
DOI: 10.4049/jimmunol.1100959
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a PIAS4 Homologue from Zebrafish: Insights into Its Conserved Negative Regulatory Mechanism in the TRIF, MAVS, and IFN Signaling Pathways during Vertebrate Evolution

Abstract: Members of the protein inhibitor of activated STAT (PIAS) family are key regulators of various human and mammalian signaling pathways, but data on their occurrence and functions in ancient vertebrates are limited. This study characterizes for the first time to our knowledge a PIAS4 homologue (PIAS4a) from zebrafish. Structurally, this zebrafish PIAS4a (zfPIAS4a) shares a number of conserved functional domains with mammalian PIAS4 proteins, including the scaffold attachment factor A/B/acinus/PIAS box, PINIT, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 72 publications
0
32
0
Order By: Relevance
“…Recently MAVS homologous genes have been identified in several fish species, including zebrafish D. rerio [21,28], Japanese flounder P. olivaceus [26], grass carp C. idella [37], common carp Cyprinus carpio [38], and pufferfish T. nigroviridis [27]. These studies have shown that fish MAVS not only activates IFN promoter but also induces the transcription of IFN and some ISGs [21,26,28,39], and that overexpression of fish MAVS confers protection on cultured fish cells against DNA and RNA virus infection [21,26,28]. However, whether fish utilize a conserved signaling pathway involving MAVSmediated IFN response remains elusive.…”
Section: Discussionmentioning
confidence: 99%
“…Recently MAVS homologous genes have been identified in several fish species, including zebrafish D. rerio [21,28], Japanese flounder P. olivaceus [26], grass carp C. idella [37], common carp Cyprinus carpio [38], and pufferfish T. nigroviridis [27]. These studies have shown that fish MAVS not only activates IFN promoter but also induces the transcription of IFN and some ISGs [21,26,28,39], and that overexpression of fish MAVS confers protection on cultured fish cells against DNA and RNA virus infection [21,26,28]. However, whether fish utilize a conserved signaling pathway involving MAVSmediated IFN response remains elusive.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, variant 1c, which lacks a C-terminal transmembrane domain, has no influence on either IRF3 or NFk B signalling pathways (Lad et al, 2008). MAVS orthologues have been identified in zebrafish (Xiong et al, 2012), salmon (Lauksund et al, 2009), Japanese flounder (Simora et al, 2010), spotted green pufferfish (Xiang et al, 2011) and grass carp (Wan et al, 2013). Although alternative splicing variants of MAVS have been reported in zebrafish and salmon (Biacchesi et al, 2009), their functions and mechanisms of interacting with other signalling proteins remain poorly understood.…”
Section: Antiviral Immunity Against Svcvmentioning
confidence: 99%
“…The encoding sequences of DrMyD88, DrTLR3, and DrTLR22 were subcloned into pCMV-Tag2B (Invitrogen) or pcDNA6/myc-HisB. The plasmids of pEGFP-TRIF and pCMV-TRIF were previously constructed in our laboratory (33). The NF-kB luciferase construct was purchased from Clontech, and the pRL-TK (Renilla luciferase reporter plasmid) vector was obtained from Promega.…”
Section: Plasmid Constructionsmentioning
confidence: 99%
“…The empty plasmid was added to ensure that all samples received equal amounts of DNA. At 24 h after microinjection, embryos were collected for luciferase activity detection as previously described (32,33). For IFN production assay, plasmids in various combinations (pEGFP-TRIF alone, pEGFP-TRIF plus DrMO, and pEGFP-TRIF plus DrMO and DrSIGIRR mRNA) were microinjected into one-cell stage embryos.…”
Section: Evaluation Of Drsigirr In Nf-kb Activation and Ifn Productionmentioning
confidence: 99%
See 1 more Smart Citation